Migrant Hospitalities in the Mediterranean Encounters with Alterity in Birth and Death - Grotti, Vanessa; Brightman, Marc (Springer Nature, 2021)
This open access book applies insights from the anthropology of hospitality to illuminate ethnographic accounts of migrant reception in various parts of the Mediterranean. The contributors ground the idea and practice of hospitality in concrete ethnographic settings and challenge how the casual usage of Derridean or Kantian notions of hospitality can blur the boundaries between social scales and between metaphor and practice. Host-guest relations are multiplied through pregnancy and childbirth, and new forms of hospitality emerge with the need to offer mortuary practices for dead strangers, helping to illuminate the spatial and scalar dimensions of morality and politics in Mediterranean migrant reception.